Introducing Plant-Based Mediterranean Diet as a Lifestyle Medicine Approach in Latin America: Opportunities Within the Chilean Context - Figueroa, Catalina; Echeverría, Guadalupe; Villarreal, Grisell; Martínez, Ximena; Ferreccio, Catterina; Rigotti, Attilio (Frontiers in Nutrition, 2021)
Latin America is experiencing a significant epidemiological and nutritional transition, with a trend toward higher incidence of food-related chronic diseases. In this context, Lifestyle Medicine (LM) is a growing field focused on assisting individuals in adopting healthy behaviors for the prevention and treatment of these chronic diseases, including, among other pillars, a great emphasis on healthy eating. There is also a growing interest worldwide in environmental sustainability of dietary patterns, with increasing concern about their effects on planetary health. In this context, whole-food, plant-based diets -such as the Mediterranean diet (MD)- have emerged as a solution for both healthier eating and lowering environmental impact. Yet in order to be effective at these goals and achieve a high adherence to any nutritional prescription, the sociocultural reality of the community or population where we aim to practice must also be taken into account. In this review, we specifically highlight the plant-based MD as a LM-contextualized dietary pattern that is adaptable, applicable and sustainable within the Chilean context and has the potential to address the current trend of chronic diseases in our country.